Assessment of the American Joint Commission on Cancer 8th Edition Staging System for Patients with Pancreatic Neuroendocrine Tumors: A Surveillance, Epidemiology, and End Results analysis. (29th January 2018) - Li, Xiaogang; Gou, Shanmiao; Liu, Zhiqiang; Ye, Zeng; Wang, Chunyou
Abstract: Although several staging systems have been proposed for pancreatic neuroendocrine tumors (pNETs), the optimal staging system remains unclear. Here, we aimed to assess the application of the newly revised 8th edition American Joint Committee on Cancer (AJCC) staging system for exocrine pancreatic carcinoma (EPC) to pNETs, in comparison with that of other staging systems. We identified pNETs patients from the Surveillance, Epidemiology, and End Results (SEER) database (2004–2014). Overall survival was analyzed using Kaplan–Meier curves with the log‐rank test. The predictive accuracy of each staging system was assessed by the concordance index (c‐index). Cox proportional hazards regression was conducted to calculate the impact of different stages. In total, 2424 patients with pNETs, including 2350 who underwent resection, were identified using SEER data. Patients with different stages were evenly stratified based on the 8th edition AJCC staging system for EPC. Kaplan–Meier curves were well separated in all patients and patients with resection using the 8th edition AJCC staging system for EPC. Moreover, the hazard ratio increased with worsening disease stage. The c‐index of the 8th edition AJCC staging system for EPC was similar to that of the other systems. For pNETs patients, the 8th edition AJCC staging system for EPC exhibits good prognostic discrimination among different stages in both all patients and those with resection. Abstract : The purpose of our study was to discuss whether the new N category (N0, N1, N2) or the 8th staging systems for PDAC is suitable for pNETs, and the results showed that the 8th staging systems for PDAC are more suitable for pNETs compared with the 8th staging systems for pNETs/ENETS.